Лекции по истории русско-українских литературных связей - Звиняцковский, Владимир (Masaryk University Press, 2023)
Title in English: Lectures on the history of Russian-Ukrainian literary relations The book contains 16 chapters, which in the form of lectures are devoted to various aspects of the history of Russian-Ukrainian literary relations, especially in the 19th and 20th centuries. Some myths still alive in the consciousness of the wider and professional public are set to the right level, and issues of double cultural identity are tehere also discussed, namely on a philosophical, historical and literary level. The book is intended for readers fluent in the Russian language from among students of philological fields focused on the East Slavic area, professional literary scholars and the wider public.